Study of superposition modulation/mapping for digital communications systems - Edy Gunawan (2014)
The capacity of a Gaussian channel can be achieved if and only if the channel outputs are Gaussian and it has been known since Shannon’s breakthrough paper in 1948. Conventional mapping schemes, like ASK, QAM or PSK suffice for approaching the Shannon limit in the low signal-to-noise ratio (SNR) regime. Meanwhile, these mapping schemes are insufficient to achieve capacity, which produce uniformly distributed symbols, in the high SNR regime. Researchers commonly resort to the technique of signal shaping that mends the symbol distribution from originally uniform into a Gaussian-like one. Superposition modulation or superposition mapping (SM) is a class of mapping techniques which use linear superposition to load binary digits onto finite-alphabet symbols. Since the output symbols of a superposition mapper can easily be made Gaussian-like, superposition mapping is of great interest for theoretical research as well as for practical implementation. Besides, the symbol constellation is typically nonbijective and its characteristic is very different from that of conventional mapping schemes. This project aims to provide a deep insight into the principles of superposition mapping. Particularly, the influence of power allocation to the system performance, both with respect to the achievable power efficiency and supportable bandwidth efficiency.